Probiotic fermented milk consumption modulates the allergic process induced by ovoalbumin in mice - Velez, Eva Maria del Mar (2015)
Orally administered probiotic micro-organisms are able to regulate the exacerbated immune response during the antigenic sensitisationprocess. The aim of the present study was to evaluate the potential efficacy of probiotic fermented milk (PFM) in preventing or treatingallergy in an experimental model, and to investigate its underlying mechanisms. Ovoalbumin (OVA)-sensitised BALB/c mice were fed withPFM before the sensitisation procedure or fed continuously with PFM. At 7 and 15 d post-sensitisation, anti-OVA-specific IgE, IgG, IgG1 and15 Q5 IgG2a concentrations were measured in the serum and broncho-alveolar lavage fluid (BALF). Concentrations of interferon-g (IFN-g), IL-4, IL-10 and total S-IgA were measured in the supernatants of macerated lungs or in the BALF. The levels of IgAþ, CD4þ and CD8þ Q6 T lymphocytes and F4/80þ cells were measured in the lungs by immunofluorescence. Inducible CD4þ/CD25/Foxp3þ regulatory T (Treg) cells were evaluated in the lungs. PFM shifted the T helper (Th)2 profile response towards a Th1 response that led to the production of IgG instead of IgE, with increasing levels of IL-10 and IFN-g that play an important role in immunomodulation exerted by PFM admin- istration in sensitised mice. Anti-OVA-specific IgE levels were significantly decreased; however, there was no modification in the levels ofanti-OVA-specific IgG and total S-IgA. PFM did not influence Treg cells in treated mice. Consumption of PFM could be a promising strategy in the amelioration of airway allergies, considering that the effect is mediated by the production of IgG through the activation of Th1instead of the direct activation of Th2 cells to produce IgE.